Voltage-activated calcium currents in octopus cells of the mouse cochlear nucleus - Bal, Ramazan; Ortel, Donata (Springer, 2007)
Octopus cells, neurons in the most posterior and dorsal part of the mammalian ventral cochlear nucleus, convey the timing of synchronous firing of auditory nerve fibers to targets in the contralateral superior paraolivary nucleus and ventral nucleus of the lateral lemniscus. The low input resistances and short time constants at rest that arise from the partial activation of a large, low-voltage-activated W conductance (g(KL)) and a large mixed-cation, hyperpolarization-activated conductance (g(h)) enable octopus cells to detect coincident firing of auditory nerve fibers with exceptional temporal precision. Octopus cells fire conventional, Na+ action potentials but a voltage-sensitive Ca2+ conductance was also detected. In this study, we explore the nature of that calcium conductance under voltage-clamp. Currents, carried by Ca2+ or Ba2+ and blocked by 0.4 mM Cd2+, were activated by depolarizations positive to -50 mV and peaked at -23 mV. At -23 mV they reached 1.1 +/- 0.1 nA in the presence of 5 mM Ca2+ and 1.6 +/- 0.1 nA in 5 mM Ba2+ Ten micromolar BAY K 8644, an agonist of high-voltage-activated L-type channels, enhanced I-Ba by 63 +/- 11% (n=8) and 150 mu M nifedipine, an antagonist of L-type channels, reduced the I-Ba by 65 +/- 5% (n=5). Meanwhile, 0.5 mu M omega-Agatoxin IVA, an antagonist of P/Q-type channels, or 1 mu M omega-conotoxin GVIA, an antagonist of N-type channels, suppressed I-Ba by 15 +/- 4% (n=5) and 9 +/- 4% (n=5), respectively. On average 16% of the current remained in the presence of the cocktail of blockers, indicative of the presence of R-type channels. Together these experiments show that octopus cells have a depolarization-sensitive gc, that is largely formed from L-type Ca2+ channels and that P/Q-, N-, and R-type channels are expressed at lower levels in octopus cells.
Keywords: voltage-sensitive calcium channels; cochlear nucleus; hearing; patch clamp; brain slices